Decoding Food Labels: Tools for People with Food Allergies - Amy H. Simonne; Elizabeth A. Gollub (EDIS)
Revised! FCS-8781, a 12-page fact sheet by Amy Simonne and Elizabeth Gollub, is a valuable resource for anyone dealing with food allergies or food intolerances. It covers egg, milk, wheat, soy, nut, and seafood allergies, as well as food additive intolerances, and lists different names these ingredients may appear under on food labels and foods they may be hidden in. Revised to include information on fish and shellfish allergies and to update links. Published by the UF Department of Family, Youth and Community Sciences, November 2007.